Arterial Oxygen Saturation (Sa02) Changes Following Pharyngeal Flap Operation - HARA, Hisanaga; TACHIMURA, Takashi; WADA, Takeshi; SATOH, Koichi (Journal of Japanese Cleft Palate Association, 1992)
For the evaluation of respiratory function following pharyngeal flap operation, arterial SaO2 was monitored with the use of pulse oxymetry. All of the 6 subjects with snoring during sleep after surgery were selected randomly, and were followed by arterial SaO2 during sleep from 0.00 a. m. to 5 a. m. for the 1st to 12th postoperation 10 days. The results obtained were as follows, 1. Slightly undulated changes of the mean arterial SaO2 to the normal lower amount (SaO2 94 %)were seen in four out of six patients during sleep in the period from the 2nd to 6th postoperation days. 2. All six patients maintained SaO2 within the normal range during sleep following the 8th postoperation day. These fi ndings may suggest that the pharyngeal flap operation, based on our method, may not cause obstructive sleep apnea, however, the monitoring of respiration for a week after operation may be recommended.